Breeding Strategy of Acacia Hybrid (Acacia mangium × A. auriculiformis) to Increase Forest Plantation Productivity in Indonesia - Sri Sunarti; Mohamad Na'iem; Eko Bhakti Hardiyanto; Sapto Indrioko (Institut Pertanian Bogor (IPB University), 2013)
Acacia hybrid (Acacia mangium× A.auriculiformis) shows better growth and wood properties, and tolerance to pest and disease. Currently, acacia hybrid breeding strategy was developed through naturally hybrid selected from trees grown in plantation. However, mass propagation of acacia hybrid using such kind of strategy was not satisfied due to ageing effect. This study was aimed to develop a new acacia hybrid breeding strategy using controlled pollination hybridization technique. The strategy was developed through a series of research: flowering, crossing, hybrid identification, clone multiplication, and clonal test. The results of study showed that the series of research for developing acacia hybrid breeding strategy was achieved. Flowering time synchronization provided a high probability for the success of controlled pollination hybridization. Leaves taxonomy at seedling stage revealed to be an efective way to identify acacia hybrid with acuracy of 92.2%. The acacia hybrid was succesfully propagated using shoot cutting at rate of 78.1%. The best selected clones of acacia hybrid outperformed in height growth at rates of 17.28% over to superior pure parents, which is equivalent to the estimated stand productivity at around 48 m3 ha-1 y-1. The series of research provided a new effective and efficient breeding strategy for acacia hybrid.